2021
DOI: 10.1080/07853890.2021.1930138
|View full text |Cite
|
Sign up to set email alerts
|

Incidence of invasive Group B Streptococcus (iGBS) infections and the factors associated with iGBS mortality in adults during 2013–2017: a retrospective study at Thailand’s largest national tertiary referral center

Abstract: Objectives To determine the incidence of invasive Group B streptococcal (iGBS) diseases and the factors significantly associated with iGBS mortality in adult patients. Material and methods This retrospective study included adults with a positive culture for GBS isolated from a sterile site at Siriraj Hospital – Thailand’s largest tertiary care hospital – during January 2013 to December 2017. Results Of the 224 included patients, 75.9% had bac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 12 publications
(7 citation statements)
references
References 21 publications
0
6
0
1
Order By: Relevance
“…The overall 90-day mortality rate in our GBS bacteremia patients was around 22%. In other studies, mainly 30-day mortality was reported, which ranged from 6.5% to 14.4%, while several of these studies also included patients without bacteremia [ 6 , 21 , 22 ], which may have reduced mortality. In a study that analyzed 12-month mortality in patients with invasive GBS infections, the mortality was 29% [ 23 ].…”
Section: Discussionmentioning
confidence: 99%
“…The overall 90-day mortality rate in our GBS bacteremia patients was around 22%. In other studies, mainly 30-day mortality was reported, which ranged from 6.5% to 14.4%, while several of these studies also included patients without bacteremia [ 6 , 21 , 22 ], which may have reduced mortality. In a study that analyzed 12-month mortality in patients with invasive GBS infections, the mortality was 29% [ 23 ].…”
Section: Discussionmentioning
confidence: 99%
“…In Thailand, reports of adult cases of invasive S. agalactiae infections are more common, with acute meningitis being one of the most common symptoms. [ 19 , 20 ] Worldwide, S. suis infection poses a threat to human health, but it is most prevalent in Thailand and Southeast Asia. An acute meningitis with hearing loss is one of the main clinical manifestations of S. suis infection.…”
Section: Discussionmentioning
confidence: 99%
“…These patients frequently have bacteremia with or without endocarditis and seeding of infection to distant organs. Cases of septic arthritis, necrotizing fasciitis, discitis, osteomyelitis, and endophthalmitis have been reported [9] , [34] , [35] . Of these endophthalmitis is of particular importance as patients frequently do not recover vision.…”
Section: Discussionmentioning
confidence: 99%